T‐RFLP Fingerprinting Analysis of Bacterial Communities in Debris Cones, Northern Victoria Land, Antarctica - Reut Sorek Abramovich; Francesco Pomati; Anne D. Jungblut; Mauro Guglielmin; Brett A. Neilan (Permafrost and Periglacial Processes)
The debris cones known as Amorphous Glacier and Boulder Clay are located in an ice‐free region in Northern Victoria Land, Antarctica, and differ in their isotopic composition, mechanisms of ice distribution, geological formation and age. However, to date it is not known if bacterial community profiles within ice and permafrost can be established for these environments, and then whether glaciological differences between the two areas would be reflected in the bacterial community composition. In order to gather first evidence for the bacterial communities in these glacial zones, we carried out terminal‐restriction fragment length polymorphism (T‐RFLP) analysis on the 16S rRNA gene using a universal bacterial amplification protocol on two permafrost cores. The DNA yields from ice‐core samples ranged from 0.29 ng μL‐1 in Amorphous Glacier to 88 ng μL‐1 in Boulder Clay. Bray‐Curtis cluster analysis suggested Boulder Clay bacterial profiles were similar to each other, but cluster separately from the Amorphous Glacier bacterial profile. Copyright © 2012 John Wiley & Sons, Ltd.